Faaliyatu Toriqotu Make a Macth Fii Ta'liimi al-Mufradat - Anyes Lathifatul Insaniyah; Maryam Rifqiyah (Institut Agama Islam Darusssalam Blokagung, 2021)
The selection of the right method in mufrodat learning must adapt to the needs of students. Because a good method is a method that is suitable for use with students' conditions during the learning process. The purpose of this study was to determine the effectiveness of the make a match method in mufrodat learning and mastery of mufrodat students of class XI MA Al-Amiriyah Blokagung Banyuwangi. The research method used is a comparative quantitative method by comparing the value of one variable with other variables at different times. The instrument in this study used a test. Data collection techniques using observation, tests, and documentation. This research was conducted using the SPSS program. Data analysis in this study was normality test and paired sample t-test (paired sample test). The results showed that the paired sample t-test was a correlation of effectiveness before using the make a match method and after using the make a match method. The magnitude of the correlation x1 and x2 is 0.608 with a significance of 0.000. And the success of using the make a match method in mastering the mufrodat which shows that the value of t count is greater than t table (10,672>2,045). Keyword: Effectiveness, Make a Macth, Vocabulary